find solution to following differential equation with initial conditions
y''+y'-2y=6e^x-2x
y(0)=2, y'(0)=0

- anonymous

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- anonymous

i am trying, give me some time, these problems are not short

- anonymous

do you have the answer from the text book?

- anonymous

1st solve y"+y'-2y=0
Charateristic Eq. m^2 + m - 2 = 0
(m+2)(m-1)=0
m=-2, m=1
so \[y_c = c_1 e ^{-2x} + c_2 e ^{?}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

then find \[y_p(x)=u_1(x)y_1(x) + u_2(x)y_2(x)\]

- anonymous

then you would need wronskian
which i am still working on, lol...

- anonymous

\[w(y_1,y_2)=3e ^{-x}\]
if anyone wants to correct any mistakes along the processes please feel free..
thanks

- anonymous

\[u_1=-(7/6)e ^{2x}-(x/3)e ^{2x}\]
this problem is really long, i am about to give up. =(

- anonymous

i got y=4xe^x +x -(e^x)/3 +(7e^-2x)/3 G.S.

- anonymous

start getting yc then the yp then y= yc+yp

- anonymous

\[u_2 = 2x - (2x/9)e ^{3x} - (2/27)e ^{3x}\]

- anonymous

thats why we ned to get the answer from the book itself...there are probably many solutions on this..

- anonymous

its not really that long!, im pretty sure we can use the method of undetermined coeffeiients but i cant seem to get a right answer to fit, i think my yp is wrong, variation of paremeters might be unessecary?

- anonymous

\[y_p = [-(7/6)e ^{2x} - (x/3)e ^{2x} ][e ^{-2x}]+[2x-(2x/9)e ^{3x}-(2/27)e ^{3x}][e ^{x}]\]

- anonymous

start w/ yc=c1e^x + c2e^-2x
yp=Ae^x +Bxe^x+Cx

- anonymous

ok then there must be other methods that will make this shorter
perhaps laplace?
or annihilator?

- anonymous

i am done, i am happy i got that far til the y_p... haha.... sorry didn't help much!

- anonymous

yp'=Ae^x +B(xe^x+e^x)+C
yp"=Ae^x+B(xe^x+e^x+e^x) now sbstitute this to the orig equation
y''+y'-2y=6e^x-2x

- anonymous

my method will still work, it just going to be long and most likely I already made a mistake

- anonymous

yes you can do it from LAPLACE and get the same answer

- anonymous

i could see lots lots lots of algebra involved with laplace!

- anonymous

after subing back in, i get
\[3Be^x -2Cx+C=6e^x-2x\]
any ideas ? haha

- anonymous

yes it might take sometimes in computing them

- anonymous

3B=6
-2C=-2
but C=0?

- anonymous

i got 2e^x +Be^x+C-2Cx=6e^x-2x

- anonymous

thats why ive been stuck on it, unless the intial conditions allow c=1

- anonymous

yes C=1

- anonymous

so whats A equal to? 0?

- anonymous

2e^x +Be^x+C-2Cx=6e^x-2x
(2+B)e^x +C-2xC=6e^x-2x

- anonymous

yes A=0

- anonymous

did you get it nor rzawad?

- anonymous

2e^x +Be^x+C-2Cx=6e^x-2x
(2+B)e^x +C-2xC=6e^x-2x
2+B=6 -> B=4
and -2xC=-2x -->C=1 now subs to Yp

- anonymous

Yp=4xe^x +x
Yc=C1e^x +C2e^-2x
Y=Yc+Yp

- anonymous

gives Y=4xe^x +x+C1e^x+C2e^-2x

- anonymous

now you can take and subs the initial condition of the equation
y(0)=2, y'(0)=0

- anonymous

so \[c_1+c_2 = 2?\]

- anonymous

Y(0)=C1+C2=2 and take the Y'=4(xe^x +e^x) +1 +C1e^x+C2e^-2x
take Y'(o)=0=4(1)+1+C1-2C2
0=5+C1-2C2
sub C1=2-C2 0=5+2-C2-2C2
C2=7/3

- anonymous

C1=2-C2=2-7/3=-1/3 now subs this to your eq

- anonymous

Y=4xe^x +x+C1e^x+C2e^-2x subst here gives
y=4xe^x +x -(e^x)/3 +(7e^-2x)/3 G.S.

- anonymous

end......

- anonymous

hope rzawad8 got the same solutions and answer..... lol

- anonymous

rzawad. where did you get this problem from?

- anonymous

\[y[x]=\frac{1}{2}+\frac{3 e^{-2 x}}{2}+x+2 e^x x \] \[y\text{''}[x]+y'[x]-2y[x]\text{=}6E{}^{\wedge}x-2x\text{//}\text{Simplify} \] \[\left\{6 e^x-2 x\right\}=6 e^x-2 x \]

- anonymous

we worked hour+ for this problem
and then look! Mathematica solved the D.E. in minute+
lol...

- anonymous

wow thats real cool whats the answer from matematica did you ty to solved it from there?

- anonymous

Even with a senior using Mathtematica it was more like and hour.

- anonymous

an hour.

- anonymous

well i just solved this prob in 15 mins lol..and hoping to get the answer from the text book from rzawad..lol

- anonymous

last sem i had this Advanced engineering math even though we had a DE subject last sem. we had to cover this type of problems

- anonymous

if anyone here is taking DE now you can email me and i might help you out with your HW etc

- anonymous

http://www.wolframalpha.com/input/?i=y%27%27%2By%27-2y%3D6e%5Ex-2x+%2C+y%280%29%3D2+%2C+y%27%280%29%3D0
wolfram will give the same answer as robtobey's

- anonymous

wow i didnt knowthere is wolfram ....lol

- anonymous

its from a past exam with no solutions dude soz,

- anonymous

ok hope you got an idea of solving of this type of prob...thnx

Looking for something else?

Not the answer you are looking for? Search for more explanations.